An association analysis of lipidome and transcriptome highlights the involvement of MmGDPD1 in regulating low phosphorus tolerance in Malus mandshurica - Hong Zhao; Yawei Wu; Luonan Shen; Zhengchun Li; Lin Deng; Xiaopeng Wen (Horticultural Plant Journal)
Phosphorus (Pi) plays a crucial role in the growth and development of plants. Membrane lipid regulation is one of the main mechanisms underlying plant adaptation to Pi deficiency. Previously, the high tolerance to low-Pi stress was justified in an elite line, MSDZ 109, which was obtained from Malus mandshurica. To better understand the mechanism underlying high adaptation to low-Pi stress, currently, lipidomic and transcriptomic analysis, as well as CRISPR/Cas9 and MmGDPD1-overexpressing methodologies were comprehensively integrated into a strategy for elucidating the high tolerance to low-Pi stress. Totally, 770 differential metabolites were identified from the roots between the low-Pi and stress-free, belonging to 21 sub-classes of lipid compounds. Fatty acids (FA) constituted the predominant lipid component, accounting for approximately 50%–60% of the total lipids, and triglycerides (TAG) ranked the second, comprising around 12% of the total, consecutively followed by phosphatidylcholine (PC) and diacylglycerol (DAG) with approximately 10% and 8% of the total, respectively. The synchronous transcriptomic analysis revealed a significant up-regulation of genes related to glycerophospholipid and glycerolipid metabolism, specifically those (e.g., MmGDPD1, MmDGDG1, MmMGDG1, MmSQDG, etc.) involved in phospholipid and galactosyl synthesis in response to low-Pi stress. GUS fusing reporter assay showed that MmGDPD1 promoter induced GUS gene expression and demonstrated initiation activity. Based on expression analysis, a dual-luciferase reporter assay, as well as yeast one-hybrid (Y1H) identification, MmPHR1 was justified to bind with the MmGDPD1 promoter and positively regulate plant tolerance to low-Pi stress. To further elucidate the role of MmGDPD1, CRISPR/Cas9 and MmGDPD1-overexpressing vectors were successfully introduced into apple (‘Royal Gala’) calli. Interestingly, the MmGDPD1-KO line calli exhibited the remarkable decreases in the contents of phosphodiesterase (PDE), activity, as well as the contents of total Pi, and Pi in comparison with those of the wild type. Conversely, MmGDPD1-OE ones demonstrated the significant elevation in Pi accumulations, further justifying its potential role in Pi remobilization in apple. Therefore, MmGDPD1 substantially involves elevating low-Pi tolerance via promoting Pi release in M. mandshurica.